Pesticide Exposure During Pregnancy Increases the Incidence of Autism - Enggal Hadi Kurniyawan; Alfid Tri Afandi; Dicky Endrian Kurniawan (Jurusan Kebidanan Poltekkes Kemenkes Padang, 2023)
Pesticides that are often used in the agricultural sector are known as organophosphate, which can affect the functionality of pregnant women and fetal bodies, both acutely and chronically. It can increase the risk of children developing autism spectrum disorders. This literature review aims to identify the type, frequency, dose, and transmission criteria of mothers who are poisoned or exposed to pesticides with the incidence of ASD in children, both pre-birth and early in life. This research uses the study methods of literature review with three online databases, namely Google Scholar, PubMed, and ScienceDirect, with publications between 2017 and 2023. The ten journals explain that Several types of pesticides, such as DDE, pyrethroids, organophosphates, and glyphosate, which are exposed to pregnant women, are associated with the incidence of autism in children in their womb. Usually, children are known to have autism at the age of 3 years or the age of 5 years. Exposure to pesticides during pregnancy can contribute to the risk of developing Autism Spectrum Disorder (ASD) in children. Some pesticides, such as organophosphates, are associated with an increased risk of ASD in children. In addition, acetic acid intake during pregnancy may affect the relationship between pesticide exposure and the risk of developing ASD in children. Health workers can conduct counseling about the dangers of exposure to peptides in fetal development for pregnant women.